DESIGN E SUSTENTABILIDADE AMBIENTAL: potencialidade de aproveitamento da pele da pescada amarela - Santos, Camila Andrade dos (2014)
For Design, the raw material chosen in the project, sometimes come from non-renewable natural resources, is the starting point for the production of any product. The increased production of goods, driven by the logic of ever increasing consumption, has implied in the use of more inputs, which is reflected in the increased exploitation of environmental resources. This chain of exploitation of natural resources has been the subject of criticism in several areas of knowledge, cause the numerous environmental problems identified worldwide. Considering the problems created by this situation, studies on Design, that taking for object of analysis the relationship between Design and development of products based on alternative raw materials, with less impact to the environment must be thinking as necessary. Taking the question of the relationship between Design and environmental sustainability as a central axis, the present work, using the methodological approach of ethnographic design, seeks to reflect on the potential use of pescada amarela (Cynoscion acoupa) as an alternative raw material for the development of products with low environmental impact, contributing to reduction of such waste in the environment.